Effect of fiber profile parameters on the transmission properties of the tapered optical fibers - Musa, Baktiar; Ismail, Alyani; Abdul Aziz, Rozi; Muhammad Noor, Ahmad Shukri; Mahdi, Mohd Adzir (IEEE (IEEE Xplore), 2011)
We fabricated a tapered optical fiber usiug a Vytran fiber tapering workstation which utilizes a filament as the heat source. The tapered fibers were fabricated with varying dimensions in order to study their effects on the transmission properties. The tapers were characterized by monitoring their transmission during and after tapering process. These transmissions were normalized to the transmission spectra of the untapered fiber. Taper angle was found to influence the transmission with larger angle contribute to a higher losses. Power loss of the best taper parameter is about 40 percent which resulted by small taper angle of 5.7mrad. Overall length of the taper also affects the transmission with shorter taper having a longer free spectral range (distance between two successive peaks in the transmission spectrum).